Autoimmune Hemolytic Anemia After Cord Blood Transplantation: A Retrospective Single-Center Experience - Yuan J; Liang ZY; Dong YJ; Ren HY (Dove Medical Press, 2023)
Jing Yuan,1 Ze-Yin Liang,2 Yu-Jun Dong,2 Han-Yun Ren2 1Department of Hematology, The Second Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Department of Hematology, Peking University First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Ze-Yin Liang; Han-Yun Ren, Department of Hematology, Peking University First Hospital, Beijing, People’s Republic of China, Email woaifeiyan1513@163.com; cinderella8886@163.comObjective: To describe the incidence, possible risk factors, and treatment options of autoimmune hemolytic anemia (AIHA) occurring after cord blood transplantation (CBT).Methods: We retrospectively analyzed the patients who underwent CBT at Peking University First Hospital between January 2004 and July 2022.Results: We totally identified thirty-six patients who received CBT. Median age was 27.5 years (range, 1.6– 52). With a median 6 (range 0.6– 10.0) years survivor follow-up, six patients developed AIHA (2 Evans syndrome included) at a median of 168 (range, 122– 264) days post-CBT for 8% cumulative incidence density 3 years. Its mortality was 50% and mainly associated with concomitant infections (CMV reactivation rate nearly 100%). The possible risk factors for developing AIHA are CMV reactivation, GvHD and HLA mismatch.Conclusion: AIHA is a clinically significant common complication in recipients post-CBT. Corticosteroids combined with intravenous immunoglobulin (IvIg) is recommended for the treatment of warm antibody AIHA after CBT.Keywords: autoimmune hemolytic anemia, cord blood transplantation, combination therapy, prognosis